(122) Artificial Neural Networks Usage for Underground Water Storage & River Nile in Toshka Are استخدام الشبكات العصبية الاصطناعية لتخزين المياه الجوفية ومياه نهر النيل في منطقة توشكى - Abdalla El-Daoushy; Amani Omar; Samir Nassar (National Planning Institute،, 2018)
December 1998.